Analysis of Chemical Simulants in Urine: A Useful Tool for Assessing Emergency Decontamination Efficacy in Human Volunteer Studies. Issue 5 (30th October 2020) - James, Thomas; Collins, Samuel; Amlôt, Richard; Marczylo, Tim
Abstract: Introduction: To date, all human studies of mass-casualty decontamination for chemical incidents have relied on the collection and analysis of external samples, including skin and hair, to determine decontamination efficacy. The removal of a simulant contaminant from the surface of the body with the assumption that this translates to reduced systemic exposure and reduced risk of secondary contamination has been the main outcome measure of these studies. Some studies have investigated systemic exposure through urinary levels of simulant metabolites. The data obtained in these studies were confounded by high background concentrations from dietary sources. The unmetabolized simulants have never been analyzed in urine for the purposes of decontamination efficacy assessment. Study Objective: Urinary simulant analysis could obviate the need to collect skin or hair samples during decontamination trials and provide a better estimate of both decontamination efficacy and systemic exposure. The study objective therefore was to determine whether gross skin contamination as part of a decontamination study would yield urine levels of simulants sufficient to evaluate systemic availability free from dietary confounders. Methods: In this study, a gas chromatography-tandem mass spectrometry method was developed for the analysis of two chemical simulants, methyl salicylate (MeS) and benzyl salicylate (BeS), in urine. An extraction and sample clean-up method was validated, enabling quantitation of these simulants in urine. The method was then applied to urine collected over a 24-hour period following simulant application to the skin of volunteers. Results: Both MeS and BeS were present in all urine samples and were significantly increased in all post-application samples. The MeS levels peaked one hour after skin application. The remaining urinary levels were variable, possibly due to additional MeS exposures such as inhalation. In contrast, the urinary excretion pattern for BeS was more typical for urinary excretion curves, increasing clearly above baseline from four hours post-dose and peaking between 12.5 and 21 hours, a pattern consistent with dermal absorption and rapid excretion. Conclusion: The authors propose BeS is a useful simulant for use in decontamination studies and that its measurement in urine can be used to model systemic exposures following skin application and therefore likely health consequences.